The Relationship Between Health Literacy and Healthy Lifestyles of Junior High School Students - Achmad Reza Firmansyah; Endang Sri Wahjuni; Sapto Wibowo (Universitas Majalengka, 2023)
A healthy lifestyle is part of self-awareness of the importance of maintaining health, so that in an effort to maintain health, information related to health is needed through l health iteration, if literacy Low health will be able to affect many things related to health such as doing inappropriate health care and lack of health-related knowledge. The purpose of this study was to determine the relationship between health literacy and the healthy lifestyle of junior high school students. This study uses a quantitative approach with a type of correlational research that connects one or more free variables with one bound variable. Instruments used HLS-EU-Q16, Newest Vital Sign, and healthy lifestyle with Healthy Lifestyle Scale. The Sample selected was Junior High School 1 Krian with a sample of 219 students. Data analysis in this study used gamma correlation and percentage data tests. The results of the study showed that there was a relationship between health literacy according to perceptions and the healthy lifestyle of junior high school students during the Covid-19 pandemic with a significant value of 0.000 < 0.05 with a contribution of 24%. As for health literacy based on functional, it showed no relationship with a significant value of 0.185 > 0.05 with a contribution of 7%.